ANTIBIOTIC PROFILE IN THE TREATMENT OF CHRONIC SUPPURATIVE OTITIS MEDIA (CSOM) AT IBNU SINA HOSPITAL IN 2023-2025 - Annisa Shezan Nazafarin; Andi Sitti Fahirah Arsal; Ahmad Ardhani Pratama; Andi Tenri Sanna; Mila Habibasari (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Chronic suppurative otitis media (CSOM) is a chronic middle ear infection characterized by tympanic membrane perforation and persistent discharge. Proper antibiotic use is crucial to prevent resistance and complications. To determine the antibiotic profile in CSOM patients at Ibnu Sina Hospital, Makassar, from January 2023 to December 2025. This descriptive observational study used a cross-sectional design with medical record data. Samples were collected using total sampling. From 50 patients (61 prescriptions), the majority were adults (48%) with an equal gender distribution (50% male, 50% female). The most common antibiotic class was $β$-lactams (67%), specifically cefixime (48%). Capsules were the most dominant dosage form (44.3%), with cefixime 200 mg as the most prescribed dose (31%). The frequency of administration was mostly twice daily (96.7%), and the most frequent duration was 5 days (36.1%). Conclusion: Antibiotic use for CSOM at Ibnu Sina Hospital is dominated by $β$-lactams (cefixime) administered empirically. While dosage and frequency align with standards, variations in treatment duration require further evaluation.